Validitas dan Reliabilitas Instrumen Penilaian Kemampuan Berpikir Tingkat Tinggi ten-tang Materi Hereditas untuk Peserta Didik SMA/MA - Nining Purnama Dewi; Yosi Laila Rahmi; Heffi Alberida; Rahmawati Darussyamsu (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
Implementation of 2013 Curriculum which is able to form students who have the ability to think at a high level as the demands of the times. One effort to develop students' higher-order thinking skills is to use appropriate assessments so that students can get used to working on higher-order thinking skills. This study aims to produce an instrument for assessing high-order thinking skills about heredity material for students of class XII SMA / MA that are valid. This study uses a 4-D models development model consisting of the stages of define, design, develop, and disseminate. However, the disseminate stage was not carried out due to limited time and money from the researchers. The subjects of this study were 3 validators, 2 biology subject teachers and 33 students of class XII MIPA 3 at SMAN 7 Padang. The data collection instrument was in the form of a validity questionnaire filled out by biology lecturers at UNP and biology subject teachers at SMAN 7 Padang. Data analysis using the ANATES 4.09 application. Based on the results of the data analysis instrument for the assessment of high-order thinking skills that have been tested, the results obtained are in the form of an instrument for assessing high-order thinking skills about heredity material for students of class XII SMA / MA that are logically very valid with a value of 93.14%, hight of empirical with a value of 74%, and very reliabel with a value of 8,4. Which can be used by teachers to measure and activate students' of higher-order thinking skills.